Measuring up to the challenge enhancing the capacity of ARAICoBeH system by enabling coral colony size measurement - Cadeliña, Patrick Lawrence P.; Yñiguez, Aletta T. (Vol. 150, No. 4 (August 2021) pages 777-788.)
"The health of many coral reefs around the globe is being threatened by a variety of local and global stressors, which makes it even more important to assess and monitor them. While the coral cover is one of the easiest and used quantifiers of reef health, the addition of coral colony sizes provides deeper insights into reef recruitment potential, fecundity, and possible environmental conditions for survivability. The use of the ARAICoBeH (A Rapid Assessment Instrument for Coastal Benthic Habitats) System can already provide similar coral cover and composition results as common methods in coral reef monitoring yet are faster and cheaper"-Title page.